Effektivisering av råvarulager för lagerhållning av ett bredare artikelsortiment - Johansson Ryytty, Matilda; Rönkkö, Linn (My University, 2014)
E2014:052, SUMMARY Inventory of raw materials holds an important role in companies within the manufacturing sector. The inventory works as a buffer that secure the supply of materials to the production unit. The aim of the inventory is to ensure that the company is able to meet the customers’ demands despite fluctuations and variations in the material flow. The size of the warehouse and the layout are physical limitations for the quantity of articles that can be stored. In addition, the quantity of articles and different types of articles are limited by the material planning. As follows, these three aspects limit the quantity of different articles that can be used in the production unit. A large supply of material to the production unit increases the flexibility towards customers and their demand. The study is carried out at Stora Enso Packagings production plant in Skene. The company desires to increase the number of different articles stored in the warehouse. This is to be able to acquire economic benefits in the production process. The study investigates how an increased number of articles could be stored in the warehouse. This is investigated through an analysis of the material planning methods and the physical layout of the warehouse. Calculations of the sizes of the stock locations and the layout of the warehouse are carried out in order to optimize the utilization of the volume of the physical warehouse without compromising efficient material handling. The result of this study shows that it is possible to lower the stock levels and increase the different types of articles in the warehouse by optimizing the material planning and the layout of the warehouse. A prerequisite to accomplish this and to secure a well-functioning material flow is valid data of the fluctuations and variations in the material flow. As a conclusion, an improved layout of the warehouse enables increased cost efficiency in the way of meeting the demands of customers. Warehouses that allow storage for a large number of different articles also offer a broad spectrum of materials for the company to use in the manufacturing process. This results in increased flexibility and ability to meet the customers’ needs. The study does not consider any economic aspects or new investments.
Keywords: Övrig industriell teknik och ekonomi; Grundläggande vetenskaper; Hållbar utveckling; Produktion; Transport; Other industrial engineering and economics; Basic Sciences; Sustainable Development; Production; Transport